Ts. Dr. Khairil Azman produces NanoPearm to increase bitumen capacity for road pavement - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2021)
GAMBANG, 6 May 2021 - A Kuching-born lecturer, Ts. Dr. Khairil Azman Masri, 33, has produced Nanopearm - Nanosilica Modified Asphalt Binder, which is a product based on nanomaterials and bitumen to increase the capacity and durability of bitumen.